Thermomechanical Behavior of Polyurethane Nanocomposite Foams Containing Organoclay Particles Modified With Bio-Based Fatty Acid - Önder, Emel; SARIER, NİHAL (Elsevier, 2024)
In this study, rigid polyurethane (PU) foams containing 1.0–2.0 wt% organoclay (OC), PU-OC, modified from nanoclay (NC) using octadecanoic acid, a bio-based chemically stable low-cost fatty acid, were synthesized and investigated for their structural, thermal and thermo-mechanical properties in comparison with pure PU and PU-NC foams. PU-OC foams provided good structural integrity and host-guest morphology. Thermogravimetric analyses revealed that the one with 2.0 wt% OC showed improved thermal stability with a significant delay in the decomposition temperatures, with maximum loss rates at 345°C and 408°C, respectively, which were at least 26 K and 8 K higher than their counterparts. PU-OC foams developed more elastic responses in dynamic mechanical tests from -80°C to +155°C and from -60°C to +60°C under cyclic compression of 0.1 N, as well as under linear deformation of 1.0–9.5N at 25°C, indicating that PU-organoclay foams are promising for use in severe environmental conditions.
Keywords: Polyurethane Foam; Nanocomposite; Organoclay; Thermomechanical Properties; DMA